AN EMPIRICAL STUDY OF THE FACTORS THAT INFLUENCE FINANCIAL DISTRESS (A CASE ON MINING INDUSTRY IN INDONESIA) - Daniella, Nicole; Lukman, Hendro (International Journal of Application on Economics and Business, 2023)
The purpose of this research is to empirically prove the role of profitability, financial leverage, and operating cash flow in predicting financial distress which can be useful for stakeholders and researchers in the future (creditors, government, and investors). This research uses quantitative research method and the data is taken from the issuer's financial statements on IDX by purposive sampling method. Multiple linear regression is used to analyze data in this research. The population used is mining industries listed on the Indonesia Stock Exchange for 7 years of observation, from 2014-2020. There are as many as 55 samples obtained in this research which are then analyzed using software Microsoft Excel and SPSS 26.0. This study shows that the profitability and operating cash flow variable have a positive effect on financial distress; variable financial leverage does not effect financial distress. Debt is a factor that can cause financial distress, so that the leverage ratio setting and debt policy must be a concern for the company, especially for mining companies that require working capital and investment in their operations.